Biblionline: v. 10, n. 2 (2014) - Bandeira, Pablo Matias (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número: http://periodicos.ufpb.br/ojs2/index.php/biblio/issue/current